Information Resources in Aleppo University and Their Sufficiency to Provide Efficient Library Service - Hasan, Mustafa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This Research Aims To Define The Information Resources In The Libraries Of Aleppo University And Their Role Inside The Academic Community Of The University. The Research Includes The Study Of Nineteen Libraries Distributed In The Following Faculties: The Civil Engineering, The Mechanic Engineering, The Electric Engineering, Architecture, Informatics Engineering, Education, And The Institute Of The Arabic Scientific Heritage. The Research Clarifies The Image Of The Academic Community Of The University Along With The Process Of Building And Improving The Information Resources In The Libraries At Aleppo University. It Also Discusses The Procedures Related To The Policy Of Building And Improving Information Resources And The Methods, Tools Of Selection Along With Maintenance, Exclusion, Covering And Inventory Process. The Research Resulted In: - Aleppo University Heavily Lacks The Preparation Of Teaching Committee Members. - There Is No Clearly Written Policy For Building And Improving Information Resources Followed By The Libraries At The University. The Same Lack Applies To The Process Of Selection.